Development of Physics Laboratory Manual: Characteristic of Resistors Circuit - Ricky Ramdani; Eka Murdani; Intan Kusumawati; Haewoon Park (JIPF (Jurnal Ilmu Pendidikan Fisika), 2019)
This study aimed to produce a physics laboratory manual characteristic of a single, series, parallel and series-parallel series of resistors; found out the quality of the physics laboratory manual characteristics of a single, series, parallel and series-parallel series of resistors. This research is a research development. Data collection in this study used suggestion and input sheets, quality assessment sheets for laboratory manual and student response sheets. Laboratory manual quality data obtained from three assessors, student response data for the limited trial I involving six students, and limited trial II involving 28 students. The physics laboratory manual characteristics of a single, series, parallel and series-parallel circuit of resistors have been produced with the criteria of "very eligible" based on final validation by media expert with a percentage of 97% and declared "very eligible" based on final validation by material expert with a percentage amounting to 83.90% and stated to be "very eligible" based on the final assessment by lecturer of electromagnetics courses with a percentage of 80%. This physics laboratory manual received a "very good" response from students with a percentage reaching 82% in limited trial I and received a "very good" response with a percentage of 82.60% in limited trial.